B186 Evaluating the timings of regional anaesthesia for rib fractures to inform service improvement within an established chest trauma pathway. (11th August 2022) - Dingle, B; Webb, R; Simpson, G; Spencer, W
Abstract : Background and Aims: We have established a multi-disciplinary chest trauma pathway within our hospital which includes guidelines for regional anaesthesia. This service is currently supported by the on-call anaesthetic team, resulting in an increased emergency theatre workload. We sought to evaluate timings of admission, referral, review, and placement of regional anaesthesia to inform service improvement. Methods: 38 patients with "rib fractures" or "chest injury" were identified via the TARN (trauma audit and research network) database over a 3 month period (Oct- Dec 2021). Exclusions included age <18, isolated sternal fracture, and direct transfer to the major trauma centre (MTC). Results: Patients had an average age of 74, Rockwood frailty score of 3.6. 40% of cases presented on weekends or bank holidays, 34% out of hours (17:00–08:00 Monday-Friday) with only 26% presenting during normal working hours (Monday-Friday 08:00–17:00). The mean time from referral to review was 5 hours 26 minutes (range 22 minutes to 21.5 hours) with an average time to block placement an additional 5 hours 40 minutes (range 33 minutes to 22 hours). Most blocks were performed out of hours (33% weekday night, 17% weekend day, and 28% weekend night), with only 22% during weekday daylight hours. Conclusions: The majority of referrals and blocks are performed out of hours which can introduce significant delays. We aim to implement a dedicated block service for catheter insertion during daylight hours, and provision of single-shot blocks out of hours with a view to improving early access to regional anaesthesia for chest trauma.